A novel self-selection bipolar RRAM cell with ultra-low operation currents for cross-point application - Gao, Bin (2013)
A self-selection and self-compliance bipolar RRAM cell based on TiN/HfOx/n+-Si structure is proposed for the CMOS compatible and ultra low power cross-point array application. Electrical forming scheme is important to achieved desired resistive switching performance due to the existing of interface sub-oxide layer. For RRAM cell, ultra-low RESET current <; 0.5 μA and good reliability (retention @ 150 °C > 104 seconds and endurance > 104 cycles) are demonstrated after optimization by material-oriented methodology. The write and read operation could be performed correctly without additional selector.